Identifying core components of a radiotherapy comfort intervention package using nominal group technique - Goldsworthy, S.; Latour, Jos; Palmer, S.; McNair, H.; Cramp, M. (2023)
Introduction: A comfortable treatment position in radiotherapy may promote patient stability and improve outcomes such as accuracy. The aim of this study was to identify, prioritise and determine the feasibility of delivery of intervention components as part of a radiotherapy comfort intervention package. Methods: Prior research, consisting of a systematic review and qualitative interviews with patient and therapeutic radiographers, was triangulated and 15 intervention components developed. An online nominal group technique consensus meeting with 7 patients who received radiotherapy exceeding 10 min for one of three anatomical cancer sites and 3 therapeutic radiographers (TRs) participated. Four activities were undertaken: 1) discussion of comfort intervention components; 2) initial vote; 3) prioritisation of intervention components; and 4) discussion of feasibility in radiotherapy and were analysed using established quantitative and qualitative methods. Results: One intervention component was added from initial discussions to the 15 pre-determined components being discussed. 11 components were recommended as ‘accepted’ (n = 5) or ‘accepted with caution’ (n = 6) to proceed to development. The highest scoring intervention components were ‘Compassionate & empathetic communication training for TRs’ and ‘Tailored information, e.g., TRs provide the required information only as part of preparation for treatment’. Anther that followed closely was ‘Adjustments & supports provided for arms or legs during treatment by TRs’. Those ‘accepted with caution’ included ‘Soft pads/mattress under the body to alleviate body discomfort managed by TRs’. Qualitative analysis highlighted concerns over the radiation environment and emphasised the importance of resources such as equipment, training, and time. Conclusion: The recommended comfort interventions have potential to improve patient comfort during radiotherapy and should be considered to incorporate into positioning and immobilisation guidelines. However, specific intervention strategies to address these components will need to be developed and robustly evaluated. Implications for practice: Comfort interventions might help patients relax and stay still during treatment, which could improve treatment accuracy and efficacy. Introducing these comfort interventions in practice have potential to lead to a more positive patient experience and improved overall quality of care during radiotherapy.